Opportunity of Next-Generation Sequencing-Based Short Tandem Repeat System for Tumor Source Identification - Chen, Anqi; Xiong, Lei; Qu, Yiling; Xi, Shihan; Tao, Ruiyang; Li, Chengtao; Zhang, Suhua (Frontiers in Oncology, 2022)
Personal identification using the tumor DNA not only plays an important role in post-operative tissue management, but also it might be the only accessible source of biological material in forensic identification. Short tandem repeat (STR) is the worldwide accepted forensic markers, however, wide-spread loss of heterozygosity (L) in tumor tissues challenges the personal identification using the conventional capillary electrophoresis (CE) based STR typing system (CE-STR). Due to the tumors are the mixtures of tumor cells and basal cells, we inferred that every germline originated allele should be detected if the detection method was sensitive enough. Next generation sequencing (NGS) is known as a high-sensitive application, which might be a promising tool for tumor source identification. In the study, we genotyped and compared the STR results between the platforms, and found the concordance was only 91.43%. Higher sensitivity did help identify more germline originated alleles as expected, and 93.89% of them could be captured by using NGS based STR system (NGS-STR). The identity-by-state (IBS) scoring system was applied to generate a new tumor source identification method based on NGS-STR, and the number of loci with 2 identical alleles (A2) proved to be an ideal criterion for the comparative larger area under receiver operating characteristic curve (ROC, AUC). Both the sensitivity and specificity were above 98% in the cut-off of A2 to distinguish the paired carcinoma (PC) sample group from the unrelated individual (UI) group, the simulated full-sibling (FS) group and the simulated parent-offspring (PO) group.